Comparison of men's and women's 100 m breaststroke performances at the 1996 Paralympic games - Daly, D.; Vanlandewijck, Y.; Malone, L.; Spaepen, A.; Steadward, R. (Education. Physical training. Sport, 1999)
Swimming competition for persons with a loco-motor disability is organised according to a functional classification system. One manner of double checking the validity of this system is to compare the race results of men and women in the same event, in this case for the 100 m breaststroke. Video recording from above water were made during the 1996 Olympic and Paralympic swimming events. In addition to the end race result, clean swimming speed, start, turn and finish time and stroke rate and length were measured for all swimmers. Men swam faster than women and had longer stroke lengths but no differences in stroke rate. Starting and turning ability did not differ. Both men and women Paralympic swimmers in the higher breaststroke classes had a higher relative starting speed than Olympic swimmers. It may be, however, that Paralympic swimmers are not starting faster but are swimming slower than Olympic swimmers. Paralympic swimmers have learned to perform the relatively uncomplicated start but not the more complex breaststroke itself. Because Paralympic swimmers may not have sufficiently mastered technique it may not be appropriate to evaluate the validity of the classification system based only on present breaststroke swimming performances.